2015
DOI: 10.1007/s13365-015-0389-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment initiation does not differentially alter neurocognitive functioning over time in youth with behaviorally acquired HIV

Abstract: Although youth living with behaviorally acquired HIV (YLWH) are at risk for cognitive impairments, the relationship of impairments to HIV and potential to improve with antiretroviral therapy (ART) are unclear. This prospective observational study was designed to examine the impact of initiation and timing of ART on neurocognitive functioning in YLWH in the Adolescent Medicine Trials Network for HIV/AIDS Interventions. Treatment naïve YLWH age 18–24 completed baseline and four additional assessments of attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
0
15
0
1
Order By: Relevance
“…Our data showing no effect of ART or current CD4 T-cells levels on attention/WM, learning, or memory agree with other studies showing that HAND persists in the ART era, with no major effect of VL, ART use, or current CD4 T-cells levels on cognitive function. In fact, a 3-year longitudinal study of young adults starting ART found no major effect of ART on attention/WM, learning, or memory (Nichols et al, 2016). A recent 4-year longitudinal study of PLWH on ART and virologically suppressed found that NCI persisted and there were no significant differences in the proportion with NCI at baseline and at 4-years (K. Robertson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showing no effect of ART or current CD4 T-cells levels on attention/WM, learning, or memory agree with other studies showing that HAND persists in the ART era, with no major effect of VL, ART use, or current CD4 T-cells levels on cognitive function. In fact, a 3-year longitudinal study of young adults starting ART found no major effect of ART on attention/WM, learning, or memory (Nichols et al, 2016). A recent 4-year longitudinal study of PLWH on ART and virologically suppressed found that NCI persisted and there were no significant differences in the proportion with NCI at baseline and at 4-years (K. Robertson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 T cell counts > 350 cells/μl who remained untreated until CD4 counts declined to <350 cells/μl; and 3. CD4 T cell counts <350 cells/μl who initiated ART at entry [16]. Plasma viral levels, CD4 counts, diagnoses, and medications were abstracted from clinic records at study visits.…”
Section: Methodsmentioning
confidence: 99%
“…YLWH were enrolled in the Adolescent Trials Network (ATN) for HIV/AIDS Interventions protocol 071/101, Assessment of Inflammatory Markers Associated with Neurocognitive Impairment in HIV-infected Adolescents , a sub-study of ATN 071, Neurocognitive Assessment in Youth Initiating ART , a 3-year longitudinal study, initiated in April 2008 with the last participant completing the study in 2013 (ClinicalTrials.gov Identifier NCT00683579) [16]. Enrollment was at 22 sites throughout the United States and Puerto Rico; procedures included routine monitoring of clinical HIV disease, neurocognitive assessments and self-reported substance use[16]. A single blood sample to assess biomarkers was obtained at week 144.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have also suggested that up to a quarter of PLWHA experience new neurocognitive impairments after initiation of HAART ( 26 ). Second, it remains unclear whether the use of antiretroviral agents with higher CPE scores confer actual and unique advantages or whether early introduction of HAART benefit HAND prospectively in the medium to longer term ( 27 ). Given these limitations, it would appear that HAART alone is an inadequate intervention for HAND.…”
Section: Contemporary and Latent Approaches To The Management Of Handmentioning
confidence: 99%